National Health and Nutrition Examination Survey I: Epidemiologic Follow-Up Study, 1987 ([Verlag nicht ermittelbar], 1993)
The National Health and Nutrition Examination Survey I Epidemiologic Follow-Up Study (NHEFS) is a longitudinal study which uses as its baseline those adult persons aged 25 to 74 years who were examined in the first National Health and Nutrition Examination Survey (NHANES I). The NHEFS surveys were designed to investigate the association between factors measured at the baseline and the development of specific health conditions. The NHEFS is comprised of a series of follow-up surveys, three of which have been completed. The first wave of data collection, the 1982-1984 NHEFS (ICPSR 8900), included all persons who were between 25 and 74 years of age at their NHANES I examination. The second wave of data collection, the 1986 NHEFS (ICPSR 9466), included the NHEFS cohort who were 55-74 years at their baseline examination and not known to be deceased at the time of the 1982-1984 NHEFS. The third wave, the 1987 NHEFS, was conducted for the entire nondeceased NHEFS cohort. The 1982-1984 NHEFS consisted of five steps. The first step focused on tracing and locating all subjects in the cohort or their proxies and determining their vital status. The second step involved obtaining death certificates for subjects who were deceased. Interviews with the participants or their proxies constituted the third phase of the follow-up. The fourth phase of the follow-up included measurements of pulse, blood pressure, and weight for interviewed respondents, and the fifth step was the acquisition of relevant hospital and nursing home records, including pathology reports and electrocardiograms. The 1986 NHEFS assessed changes to the health and functional status of the oldest members of the NHEFS cohort since the last contact period. The 1987 NHEFS also collected information on changes in the health and functional status of the NHEFS cohort since the last contact period. The Vital and Tracing Status file contains summary information about the status of the entire NHEFS cohort. The Health Care Facility Record file contains information on reports of stays in hospitals and nursing homes as well as information abstracted from facility medical records. The Mortality Data file contains data abstracted from the death certificates from all three NHEFS surveys. The Interview Data file contains information on selected aspects of the subject's health history since the time of the NHANES I exam.